MODEL SPASIAL KERENTANAN DIKAWASAN PESISIR SELATAN TELUK BETUNG KOTA BANDAR LAMPUNG TERHADAP BENCANA TSUNAMI - Adrian Adrian (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2016)
ABSTRACT Bandar Lampung is an area in Indonesia which has a high level of Tsunami threat. It is due to the position of Bandar Lampung which is located relatively near the meeting point of Indo-Australian plate dan the Eurasian plate; both are plates are relatively active. Other causes are earthquake threat and the existence of Krakatoa which is potential to generate earthquakes which are followed by a Tsunami. The data analysis showed that the potential Tsunami hazard in the coastal city of Bandar Lampung is the predicted distance run up the marinade tsunami that reached a height of 20 meters above sea level. Potential hazards include four districts, i.e. Bumi Waras District, Panjang District, South Teluk Betung District, and East Teluk Betung District. The research method is Cell-Based modeling, the one using the tool model builder in Arc GIS with 1 meter raster grid analysis, which can show and explain in detail the attributes that exist in the region. From Quick Bird image that has of 0.6 meter resolution, the existing condition of the land use can be clearly seen. The results of the analysis showed the vulnerability of Tsunami in the city of Bandar Lampung. The results showed that Bumi Waras District has the highest vulnerability level at Bumi Waras Subdistrict with an area of 85.62 Ha. Panjang District has the highest level of vulnerability at Pidada Subdistrict with an area of 30.16 ha. South Teluk Betung District has the highest level of vulnerability at Pesawahan Subdistrict with an area of 0,02 Ha. East Teluk Betung District has the highest level of vulnerability at Kota Karang Subdistrict with an area of 32.11 Ha. Keywords: Tsunami disaster, Vulnerability and cell-based modeling